2012
DOI: 10.1111/j.1574-6968.2012.02604.x
|View full text |Cite
|
Sign up to set email alerts
|

Carotenogenesis gene cluster and phytoene desaturase catalyzing both three- and four-step desaturations from Rhodobacter azotoformans

Abstract: A carotenogenesis gene cluster from the purple nonsulfur photosynthetic bacterium Rhodobacter azotoformans CGMCC 6086 was cloned. A total of eight carotenogenesis genes ( crtA , crtI , crtB , tspO , crtC , crtD , crtE , and crtF ) were located in two separate regions within the genome, a 4.9 kb region containing four clustered genes of crtAIB - tspO and a 5.3 kb region containing four clustered genes of crtCDEF . The organization was unusual for a carotenogenesis gene cluster in purple photosynthetic bacteria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Recently, the CrtI from Rba. azotoformans was also found to be capable of catalyzing both three-and four-step desaturations of phytoene to produce neurosporene and lycopene in vitro [37]. Our results demonstrated that CrtI could catalyze both three-and four-step desaturations of phytoene in vivo to produce neurosporene and lycopene in Rba.…”
Section: Discussionsupporting
confidence: 52%
“…Recently, the CrtI from Rba. azotoformans was also found to be capable of catalyzing both three-and four-step desaturations of phytoene to produce neurosporene and lycopene in vitro [37]. Our results demonstrated that CrtI could catalyze both three-and four-step desaturations of phytoene in vivo to produce neurosporene and lycopene in Rba.…”
Section: Discussionsupporting
confidence: 52%
“…In conjunction with the four-step phytoene desaturase that yields lycopene, a five-step desaturase was used to produce 3,5-didehydrolycopene (Zhang et al, 2012). Instead, carotenogenic genes from different bacteria are combined employing unique pathways that maintain altered product specificities in a simple E. coli host expressing the biosynthetic machinery for phytoene production.…”
Section: Directed Evolution and Molecular Breeding Techniques For Thementioning
confidence: 99%
“…The first type has the classical organization of crtEXYIBZ , the second type has an organization of crtE-idi-crtXYIBZ , and the third type has an organization of crtE-idi-crtYIBZ . Although different microorganisms contain the similar gene cluster, they could produce different carotenoids [5][8]. This might depend on their living environment, because carotenoids with different structures show different effect on membrane fluidity and thermo stability [9].…”
Section: Introductionmentioning
confidence: 99%